Phase and Amplitude Changes in Rainfall Annual Cycle Over Global Land Monsoon Regions Under Global Warming - Songxin Lv; Fengfei Song; Hongqiang Dong; Lixin Wu (Geophysical Research Letters)
Abstract Land monsoon rainfall has a distinct annual cycle. Under global warming, whether the phase and amplitude of this annual cycle would be changed is still unclear. Here, a global investigation is conducted using 34 CMIP6 and 34 CMIP5 models under a high emission scenario. Seasonal delays would occur in the Southern Hemisphere (SH) American (3.43 days), Northern Hemisphere (NH) African (5.98 days) and SH African (3.76 days) monsoon regions, while no robust signal is found in other monsoon regions. Except NH American monsoon, amplitude is enhanced in all the monsoon regions. Compared to amplitude, the phase changes dominate the future changes of precipitation in the SH American, NH African and SH African monsoon regions. In these phase‐dominated regions, atmospheric energetic framework is proved to be reliable at regional scale and the enhanced effective atmospheric heat capacity is found to be the dominant factor.